Agamben, g. el misterio del mal. benedicto xvi y el fin de los tiempos (2014)
Agamben, G. El misterio del  mal. Benedicto XVI y el fin de los tiempos.  D’ Meza, María Teresa (trad.). Buenos Aires: Adriana Hidalgo, 2013. 83 pp.